2022
DOI: 10.3390/life12081274
|View full text |Cite
|
Sign up to set email alerts
|

The Insulin-like Growth Factor System and Colorectal Cancer

Abstract: Insulin-like growth factors (IGFs) are peptides which exert mitogenic, endocrine and cytokine activities. Together with their receptors, binding proteins and associated molecules, they participate in numerous pathophysiological processes, including cancer development. Colorectal cancer (CRC) is a disease with high incidence and mortality rates worldwide, whose etiology usually represents a combination of the environmental and genetic factors. IGFs are most often increased in CRC, enabling excessive autocrine/p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 222 publications
0
6
0
Order By: Relevance
“…Intriguingly, increased serum miR-27a level was correlated with elevated levels of IGFBP3 in overall CRC patients, suggesting their concordant expression in CRC. Although there is a consensus of increased serum IGF1 and reduced IGFBP3 levels in CRC patients, thus increasing IGF1 availability and its mitogenic power 67 69 , a similar Egyptian report demonstrated reduced levels of serum IGF1 in overall CRC patients and average weight and overweight/obese CRC patients compared with their corresponding controls 36 . Similar to the present results, this later study revealed IGF1 as a negative variable associated with the risk of CRC in overweight/obese patients in the univariate analysis 36 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Intriguingly, increased serum miR-27a level was correlated with elevated levels of IGFBP3 in overall CRC patients, suggesting their concordant expression in CRC. Although there is a consensus of increased serum IGF1 and reduced IGFBP3 levels in CRC patients, thus increasing IGF1 availability and its mitogenic power 67 69 , a similar Egyptian report demonstrated reduced levels of serum IGF1 in overall CRC patients and average weight and overweight/obese CRC patients compared with their corresponding controls 36 . Similar to the present results, this later study revealed IGF1 as a negative variable associated with the risk of CRC in overweight/obese patients in the univariate analysis 36 .…”
Section: Discussionmentioning
confidence: 95%
“…miR-27a is also a master regulator of metabolic reprogramming in cancer cells via regulating AMP-activated protein kinase and mammalian target of rapamycin signaling pathways in CRC patients and cell lines 65 . In addition, miR-27a could affect adipocyte and cancer cell metabolism by regulating its target IGF1 17 , 32 , 66 , based on the major role of the insulin/IGF system in inhibiting apoptosis and enhancing CRC cell proliferation, differentiation, and chemoresistance 67 , 68 . Indeed, the mechanistic influence of MEG3/miR-27a/IGF1 axis was described in a prior study on periodontitis 66 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, by preventing cell division, IGFBP-2 overproduction during colorectal carcinogenesis slows the formation of tumors. The sensitivity may be improved by combining IGFBP-2 with additional biomarkers, such as CEA (Gligorijević et al, 2022). Zhu et al (2019) found that IGFBP2 overexpression promoted CRC cell proliferation and migration by suppressing E-cadherin expression and enhancing cell growth.…”
Section: Pyruvate Kinase Muscle Isozyme M2 (Pkm2)mentioning
confidence: 99%
“…IGF-2 binding to IGF-1R/IR mainly triggers the intracellular phosphorylation cascade effect to transduce downstream signals through the classical mitogen-activated protein kinase (MAPK) and phosphatidylinositol-3-kinase/protein kinase B (PI3K/Akt) pathways [ 49 ]. The receptor’s intrinsic tyrosine kinase is activated when it is combined with IGF-2, leading to the autophosphorylation of tyrosine residues within the intracellular β-subunit, then recruits insulin receptor substrates (IRS) 1–4, further binds to and activates PI3K and Akt, and ultimately activates downstream signaling molecules, such as Bad, which can inhibit cell apoptosis.…”
Section: Igf-2mentioning
confidence: 99%